Integration of three stomatological specialties in the prosthetic treatment - Ayvanka León Quintela; Humberto Manuel Rodríguez Rey; María Luisa Duque de Estrada Bertot (Centro Provincial de Información de Ciencias Médicas, 2021)
Dental implants are an option of cosmetic, functional and harmonic repairs whose rate of success is higher than 95 %. The case report of a 24 years patient is presented. She was assisted in the Orthodontics Service of Mártires del Moncada Teaching Provincial Stomatological Clinic in Santiago de Cuba and was referred from the Stomatological Prosthesis Service, with the purpose of achieving the appropriate space to place an implant, because she had lost a tooth due to dental decay since she was approximately 12 years. The prosthetic repair by means of dental implant provided an excellent result.